Drosophila heparan sulfate 6-O endosulfatase regulates Wingless morphogen gradient formation - Kleinschmit, Adam (2010)
Heparan sulfate proteoglycans (HSPGs) play critical roles in the distribution and signaling of growth factors, but the molecular mechanisms regulating HSPG function are poorly understood. Here, we characterized Sulf1, which is a Drosophila member of the HS 6-O endosulfatase class of HS modifying enzymes. Our genetic and biochemical analyses show that Sulf1 acts as a novel regulator of the Wg morphogen gradient by modulating the sulfation status of HS on the cell surface in the developing wing. Sulf1 affects gradient formation by influencing the stability and distribution of Wg. We also demonstrate that expression of Sulf1 is induced by Wg signaling itself. Thus, Sulf1 participates in a feedback loop, potentially stabilizing the shape of the Wg gradient. Our study shows that the modification of HS fine structure provides a novel mechanism for the regulation of morphogen gradients.